The benefits of PDO threads in facial rejuvenation (Research, Society and Development, 2023)
Orofacial harmonization (HOF) encompasses specialized techniques to promote facial aesthetics and health, enhancing natural beauty and non-invasively correcting imperfections. Benefits include increased self-esteem, a rejuvenated, symmetrical appearance, and improved facial muscle function. An innovative technique in this field is the use of Polydioxanone PDO threads, which are inserted under the skin, providing an immediate lifting effect and stimulating collagen production. These threads are safe and biocompatible, offering a reliable alternative to improve skin firmness and support, reduce wrinkles and expression lines without the need for surgery. They can be applied to different areas of the face, resulting in a rejuvenated and natural appearance, with long-lasting results and reduced recovery time. Thus, the objective of this narrative review of the literature is to comprehensively and thoroughly explore HOF techniques, with a special focus on the benefits and impressive results provided by the use of PDO threads.